catena-Poly[[aqua(4-ethylbenzoic acid-κO)lanthanum(III)]-tri-μ-4-ethylbenzoato] - Juan Yang; Jiantong Li; Qiufen Wang (Acta Crystallographica Section E, 2010)
The reaction of lanthanum nitrate and 4-ethylbenzoic acid (EBAH) in aqueous solution yielded the title polymer, [La(C9H9O2)3(C9H10O2)(H2O)]n. The asymmetric unit contains one LaIII atom, three 4-ethylbenzoate (EBA) ligands, one neutral EBAH ligand and one coordinated water molecule. Each LaIII ion is eight-coordinated by six O atoms from six bridging-bidentate EBA ligands, one O atom from a monodentate EBAH ligand and one water O atom in a distorted bicapped trigonal-prismatic geometry. The adjacent LaIII ions are linked by the carboxylate groups of EBA ligands in a bridging-bidetate coordination mode, resulting in an infinite chain structure along the c axis. O—H...O hydrogen-bonding interactions involving the water molecules, carboxylate groups and carboxyl H atoms are formed within the one-dimensional polymer. One of the ethyl groups is disordered over two positions with occupancies of 0.717 (7) and 0.283 (7).